Scheme Configuration of Deformable Spherical Robots Based on Fuzzy Rough Number - Fang Shihao; Qin Jianjun; Cao Yu; Shao Pai; Liu Xingjie (Jixie chuandong)
Aiming at the problem of subjectivity and uncertainty in the configuration and selection of spherical robot design schemes in multi-demand unstructured environments, a scheme evaluation method coupled with fuzzy rough number and complex proportional assessment (COPRAS） is proposed. Considering the importance relation between different demand characteristic indexes in scheme design, the quantitative analysis of demand characteristic indexes is realized based on the fuzzy rough number. The COPRAS method is used to comprehensively evaluate all alternative design schemes, the priority ranking of all alternative design schemes is obtained according to the utility index to determine the optimal configuration scheme， and the selection of deformed spherical robots is taken as an example for evaluation and verification. The research results show that the method has good reliability and practicability, which provides effective reference for the configuration and selection of the robot design scheme in the future.